#TITLE_ALTERNATIVE# - MUSFIANDINI ZAHRA (NIM. 15311017),
The fulfillment of clean water supply in Indonesia has to be the major priority that must be addressed due to its importance towards the viability of society. For urban areas, water supply systems can be done with non-piping and piping systems. Piping systems managed by the Regional Water Company (PDAM) and non-piping system managed by the community, both individually and collectively. This experiment uses a simple drinking water treatment installation consisting of pre chlorination with Ca(OCl2), aeration using multiple tray aerator with gravel media, and filtration with sand & activated carbon media. Hopefully with these units, certain parameters can be removed. Furthermore, the purpose of this experiment is to test the performance of the installation to remove iron, manganese, organic substances, total dissolved solid (TDS), and turbidity. The quality of the water effluent is tested in laboratory to review the parameters which refers to National Standard of Indonesia (SNI). The experiment was conducted with variations of additional unit which were filtration, filtration & aeration, and filtration, aeration & pre-chlorination. Variations of the flow rate operation on filtration unit are 1 LPM, 3 LPM and 5 LPM. Whereas the variations of aeration time on aeration unit are 30 minutes, 45 minutes and 60 minutes. From this experiment, the optimum flowrate is 3 LPM and the optimum aeration time is 45 minutes. The installation has achieved a great performance because the water effluent quality from this installation has met almost all of the quality standards based on Regulation of Health Ministry No. 492/2010, except for TDS which was still exceeding the quality standards. The optimum condition occurs when the units of aeration, filtration and pre-chlorination are implemented. With the removal efficiency for iron is 98,7%, manganese 83,4%, organic matterials 75,2%, TDS 3,56% and turbidity 98,5%.